HUBUNGAN KADAR GLUKOSA DARAH DAN TEKANAN DARAH PADA KOMUNITAS LANSIA RW.IX KELURAHAN SENDANGMULYO KECAMATAN TEMBALANG KOTA SEMARANG - FITRIANI KAHAR (NHM PRESS, 2022)
Diabetes Mellitus (DM) is a metabolic disorder characterized by increased blood glucose levels exceeding normal limits or hyperglycemic conditions due to impaired insulin secretion, insulin performance, or both. Two out of three people with diabetes mellitus have high blood pressure or hypertension. Hyperglycemia is often accompanied by the onset of the metabolic syndrome, namely hypertension, dyslipidemia, obesity, endothelial dysfunction and prothrombotic factors, all of which will trigger and exacerbate cardiovascular complications. This research method uses analytical observation with a cross sectional research design. The population in this study were 47 elderly people. Then the population was sampled using purposive sampling method and obtained a sample of 36 elderly respondents. Assessment of blood glucose levels using a glucometer. While the measurement of blood pressure using a sphygmomanometer. Analysis using Chi-square test. This test is said to have a significant relationship if the p value <0.05. Through testing, the results obtained were 36 elderly respondents with an age range of 45 years to > 70 years, consisting of 41.7% men and 58.3% women. The blood glucose level with a value of 70 – 110 mg/dL is included in the normal category which is 52.8%, while for normal blood pressure with a value range of 90/60 mmHg – 120/80 mmHg it is 5.6%. The significance value (p) for the correlation test between blood glucose levels and blood pressure is 0.935. This value is greater than 0.05 (p > 0.05), which means that there is no relationship between blood glucose levels and blood pressure at the Elderly Health Examination in the Elderly Community RW.IX, Sendangmulyo Village. Where the conclusion is there is no significant relationship between blood glucose levels and blood pressure in the elderly in the Elderly Community RW.IX Sendangmulyo Village, Tembalang District, Semarang City.